2016
DOI: 10.3389/fmicb.2016.00175
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of the Master Regulator XYR1 in Trichoderma reesei by Global Transcriptional Analysis

Abstract: We defined the role of the transcriptional factor—XYR1—in the filamentous fungus Trichoderma reesei during cellulosic material degradation. In this regard, we performed a global transcriptome analysis using RNA-Seq of the Δxyr1 mutant strain of T. reesei compared with the parental strain QM9414 grown in the presence of cellulose, sophorose, and glucose as sole carbon sources. We found that 5885 genes were expressed differentially under the three tested carbon sources. Of these, 322 genes were upregulated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 98 publications
4
92
1
4
Order By: Relevance
“…In this study, we performed bioinformatics approaches to search for putative CRZ1 binding sites in promoter regions of holocellulases, Ca 2+ and sugar transporter coding genes in T. reesei QM6a. Here we identified that differentially expressed holocellulases genes of this fungus [22] harbored sense and antisense CRZ1 putative binding sites at their ATG upstream sequences and it supports the evidence of the regulation played by this TF independently on carbon source availability. To be clear that CRZ1 was involved in gene regulation in the wild type strain of T. reesei , our study reports that holocellulases genes were directly or either indirectly modulated by this protein, corroborating the occurrences of putative CRZ1 binding sites sequences into T. reesei genome.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In this study, we performed bioinformatics approaches to search for putative CRZ1 binding sites in promoter regions of holocellulases, Ca 2+ and sugar transporter coding genes in T. reesei QM6a. Here we identified that differentially expressed holocellulases genes of this fungus [22] harbored sense and antisense CRZ1 putative binding sites at their ATG upstream sequences and it supports the evidence of the regulation played by this TF independently on carbon source availability. To be clear that CRZ1 was involved in gene regulation in the wild type strain of T. reesei , our study reports that holocellulases genes were directly or either indirectly modulated by this protein, corroborating the occurrences of putative CRZ1 binding sites sequences into T. reesei genome.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, differential gene expression was discussed by Castro et al [20] and Antonieto et al [21] in studies which reported the influence of carbon source on holocellulases transcription. Robust techniques as RNA sequencing have already highlighted the importance of sugar availability on the regulation mediated by transcription factors in T. reesei [22], evidencing the growing need of elucidating deep layers of regulation in this fungus.…”
Section: Introductionmentioning
confidence: 99%
“…4). Although some sugar transporters are known to be regulated by transcription factors that regulate CAZymes as well [34, 64], the observed differences between the expression profiles of transporters and CAZymes suggest that different set of regulators might be controlling the expression of these genes.
Fig. 5Expression profile of genes encoding transporters in A. niger N402 and T. reesei RUT-C30 transcriptomes.
…”
Section: Resultsmentioning
confidence: 99%
“…These results implied that the ABC transporters are inconsistent for the expression trends of (hemi)cellulase genes that might be coregulated by Xyr1. By contrast, two ABC transporters (Tr 2687 and Tr 58366) were reported downregulated under the cellulose or glucose condition in the Δ xyr1 mutant strain compared to its parental strain Qm9414 [16]. Another nine MFS transporter genes also exhibited increased expression levels after deletion of xyr1 under lignocellulose-inducing conditions (Table S11).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, transcription profiling of the T. reesei Qm 9414 and its Δ xyr1 mutant grown on cellulose, sophorose, and glucose were performed and defined the role of the transcriptional factor Xyr1 during cellulose degradation [16]. T. reesei mutant Rut-C30 is a hyperproducer of cellulolytic enzymes with its genome has been released [3, 17, 18].…”
Section: Introductionmentioning
confidence: 99%